Pemanfaatan Artificial Intelligent (AI) sebagai Sarana Informasi Layanan di UPT Perpustakaan Universitas Andalas (UNAND) - Beni Adri Yassin (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This research is an initial study on the utilization of Canva AI as an information service tool at the UPT Library of UNAND. This research approach uses a qualitative descriptive method. Data collection was conducted using documentation and interview techniques with research subjects who are active students and visit the UNAND Library twice a week. The research subjects were determined to be 12 students. As research subjects, the students were given the opportunity to evaluate the service video at the UPT Library of UNAND, which was created using the Canva AI application. The steps for determining the subjects were established through the research workflow. The research steps include topic selection, data collection from library sources, data analysis, report preparation, and presentation of research results. The research results show that the use of AI-based videos through Canva helps improve students' understanding of library services and has the potential to increase visit interest. The use of technology combined with Canva and artificial intelligence provides a different touch in the literacy of library patrons. The use of AI in libraries has become an important strategy in supporting adaptive and inclusive information services.